ANALISIS DAMPAK DARI MODEL KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN PADA DINAS PENDIDIKAN KABUPATEN BANYUASIN - Hasyim Hasyim; Syahrizal Syahrizal (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to analyze the impact of the leadership model on employee motivation at the Banyuasin Regency Education Office. Leadership models have an important role in influencing employee work motivation, which in turn can have an impact on organizational performance and productivity. In this study, the population that is the focus is employees of the Banyuasin Regency Education Office. The research method used is a survey using a questionnaire as a data collection tool. The research sample was taken using the purposive sampling method, which involved employees from various levels and work units at the Banyuasin Regency Education Office. The collected data were analyzed using descriptive statistical techniques and regression analysis to test the relationship between leadership models and work motivation. The results of this study are expected to provide a better understanding of the impact of the leadership model on employee work motivation at the Banyuasin Regency Education Office. The findings of this study are expected to provide input for organizational management in developing effective leadership strategies to increase employee work motivation. In addition, this research can also contribute to further research in the field of leadership and work motivation